Perbandingan Distance Metric pada Nearest Neighbour untuk Klasifikasi Sel Darah Putih - Felix Indra Kurniadi; Vinnia Kemala Putri (Ultimatics : Jurnal Teknik Informatika, 2019)
White blood cells, have a function to protect human body from viruses, bacteria and any other harmful substance. In this research, Local Binary Pattern was proposed for feature extraction using Euclidean distance, Chebyshev distance and Minkowski distance as classifier.